2020
DOI: 10.1038/s41598-020-59675-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide and expression pattern analysis of JAZ family involved in stress responses and postharvest processing treatments in Camellia sinensis

Abstract: the JASMONATE-ZIM DOMAIN (JAZ) family genes are key repressors in the jasmonic acid signal transduction pathway. Recently, the JAZ gene family has been systematically characterized in many plants. However, this gene family has not been explored in the tea plant. In this study, 13 CsJAZ genes were identified in the tea plant genome. Phylogenetic analysis showed that the JAZ proteins from tea and other plants clustered into 11 sub-groups. The CsJAZ gene transcriptional regulatory network predictive and expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 64 publications
1
36
0
Order By: Relevance
“…The CsPPD subfamily, which has the same TIFY motif, was also clustered with CsJAZs together in both polygenetic trees, confirming that PPD proteins may be the evolutionary precursors of JAZ and may have evolved as two independent subfamilies by gene duplication in vascular plants [1,6]. A recent study reported that 12 CsJAZ proteins were found through TIFY and Jas domain blast in tea plants [31]. Among the 12 CsJAZ proteins, six members were identical to those in our study, and the other six CsJAZ proteins in the above study both contain the so-called Jas domain, which was only part of the CCT domain but was not a true Jas domain.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…The CsPPD subfamily, which has the same TIFY motif, was also clustered with CsJAZs together in both polygenetic trees, confirming that PPD proteins may be the evolutionary precursors of JAZ and may have evolved as two independent subfamilies by gene duplication in vascular plants [1,6]. A recent study reported that 12 CsJAZ proteins were found through TIFY and Jas domain blast in tea plants [31]. Among the 12 CsJAZ proteins, six members were identical to those in our study, and the other six CsJAZ proteins in the above study both contain the so-called Jas domain, which was only part of the CCT domain but was not a true Jas domain.…”
Section: Discussionmentioning
confidence: 61%
“…The phylogenetic tree showed that the stronger inducible genes CsJAZ1, CsJAZ2, CsJAZ7, and CsJAZ8 were grouped closer than CsJAZ3 and CsJAZ4, which may suggest that JA-induced CsTIFY genes evolved from common ancestors responsive to JA [7,37]. The identical CsJAZ genes found in a previous study showed that CsJAZ2, CsJAZ3, and CsJAZ4 were remarkably upregulated by MeJA [31]. This difference may be attributable to such factors as different tea varieties, discrepancies in the elicitation effects of JA and MeJA, and differing treatment concentrations.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations